Sifat Kimia dan Sensoris Stik Berbasis Tepung Pisang (Musa paradisiaca) dan Tepung Kecambah Kacang Merah (Phaseolus vulgaris L.) - Kinayomi, Vanesha; Wisaniyasa, Ni Wayan; Ari Yusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
Stick is one of the snacks in the form of a thin long flat made of flour, has a savory taste and a crunchy texture. Banana flour and red bean sprouts flour are nutritious local food commodities and have the potential to replace wheat flour. This research aims to determine the effect of the comparison of banana flour and red bean sprouts flour and to find out the right comparison to produce the sticks with the best characteristic. Completely Randomized Design (CRD) was used with a comparison of banana flour and red bean sprouts flour which consists of 5 treatments, namely: 100%:0%, 80%:20%, 60%:40%, 40%:60%, 20%:80%. Those treatments were repeated 3 times, so 15 experimental units were obtained. The data obtained were analyzed with analysis of variance and if the treatment had a significant effect, it was continued with Duncan Multiple Range Test (DMRT). The result showed that the comparison of banana flour and red bean sprouts flour had a significant effect on water content, ash content, protein content, fat content, carbohydrates content, crude fiber content, and hedonic test (colour, aroma, taste, texture, and overall acceptance). The comparison of 40% banana flour and 60% red bean sprouts flour had the best chemical and sensory characteristics with 3,89% water content, 2,22% ash content, 13,34% protein content, 20,78% fat content, 59,75% carbohydrate content, 6,24% crude fuber content, very liked color, liked aroma, very liked taste, liked texture, also liked overall acceptance.